Improvement of the products quality level by competent experts - Гунькало, Алла Василівна; Шпак, Оксана Іванівна (Technology audit and production reserves, 2014)
Planning of improvement of the product quality level should be based primarily on the thorough study of the current and future demands for production, analyzing consumer reviews, competent expert opinion, qualified personnel etc. The algorithm of the product quality improvement by the example of diesel fuel to ensure its competitiveness in the oil market has been suggested. The algorithm provides comparing of the current quality values taking into account the suggested quality boundaries and customer satisfaction level about the quality of products. The suggested quality boundaries make it possible to determine the level of consumer needs satisfaction and decide on the sufficiency of improving product quality. The entire evaluation and quality improving procedure of products should take place under the supervision of competent experts in a certain field.